Dietary Analysis Based on 18S rDNA, and Stable Carbon and Nitrogen Isotopes in Juvenile Eriocheir sinensis Crabs Reared Under Three Feeding Modes - Lu, Zhenzhen; Sun, Yunfei; Xiao, Changlun; Cheng, Yongxu (Frontiers in Marine Science, 2021)
To investigate the growth and feeding conditions of the Chinese mitten crab Eriocheir sinensis under different feeding modes: traditional (mainly consisting of wheat, bran, and soybean meal), formulated, and mixed feeds (1:1 mixture of traditional and formulated feeds) were fed in different crab breeding ponds in this study. During the experiment, the stomach contents of juvenile crabs under the different feeding modes were collected. The main potential eukaryotic food components were studied using 18S ribosomal DNA sequencing, and the contribution of different feeding modes to the feeding source of juvenile crabs were analyzed using C and N stable isotopes. The terminal weight and weight gain rate of crabs under the formulated feeding mode were significantly higher than those in the traditional and mixed feeding modes (P < 0.05). No differences were observed in the diversity and abundance of the main potential eukaryotic feed components of male and female crabs under different feeding modes (P > 0.05). Thirty-four phyla, composed mainly of benthic organisms, were identified, with Arthropoda (mainly including Malacostraca, 30.25–51.48%), Phragmoplastophyta (mainly including Embryophyta and Trebouxiophyceae, 5.08–24.74%), and Diatomea (3.13–8.43%) being the most abundant. The δ13C and δ15N values of the feeding sources and muscle of crabs ranged from −34.45 to −22.21‰, and from 0.27 to 5.66‰, respectively, varying greatly among the three feeding modes and δ15N value of muscle under formulated feeding mode was significantly higher than that in traditional feeding mode (P < 0.05). The proportion of particulate organic matter (11.92–17.50%) is similar to Alternanthera philoxeroides (11.24–16.03%) in three feeding modes. There was no significant difference in feeding habits between male and female crabs under the same and different feeding modes. Juvenile crabs feed on both plant- and animal-based feeds in an aquaculture pond, but they are not complete predators and selectively feed on animal or plant feeds as supplements of that which is deficient, in addition to their main feed.